1992
DOI: 10.1007/bf00216246
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ecotoxicity of copper and cadmium to the zebra mussel Dreissena polymorpha

Abstract: In order to evaluate ecological consequences of the long-term presence of metals in aquatic ecosystems, we investigated the filtration rate and survival of zebra mussels (Dreissena polymorpha) during chronic exposure to Cu and Cd. The filtration rate was measured once a week in laboratory experiments lasting 9-11 weeks. The lowest Cu concentration tested (13 micrograms/L) did not affect the filtration rate and survival of D. polymorpha, but the lowest Cd concentration (9 micrograms/L) did affect the filtration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 26 publications
4
19
1
2
Order By: Relevance
“…Relatively low ACR's were observed for Cu and Zn, indicating that the effects of these metals increase with time, but not dramatically. The ACR for Cd was high, caused by a strong decrease of the ECs0 with time, as reported by Kraak et al (1992). Our results for Pb deviate from those of Kenaga (1982), since the ACR for this metal is as low as the one for the essential metal Zn.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Relatively low ACR's were observed for Cu and Zn, indicating that the effects of these metals increase with time, but not dramatically. The ACR for Cd was high, caused by a strong decrease of the ECs0 with time, as reported by Kraak et al (1992). Our results for Pb deviate from those of Kenaga (1982), since the ACR for this metal is as low as the one for the essential metal Zn.…”
Section: Discussioncontrasting
confidence: 54%
“…Kenaga (1982) calculated acute-chronic ratios (ACR; the acute ECs0 divided by the chronic ECs0) for a number of substances and organisms and demonstrated that for Daphnia magna the ACRs for Pb and Cd were much higher than for Zn and Cu, possibly because Cu and Zn are essential metals, whereas Pb and Cd are not known to have any biological function. Kraak et al (1992) observed that the ECs0 for Cd for filtration rate of the zebra mussel Dreissena polymorpha decreased when exposure time was increased from 48 h to 10 weeks, whereas the effects of Cu did not increase during prolonged exposure. This seems to support the idea that during chronic exposure the effects of non-essential metals increase more than the effects of essential metals.…”
Section: Introductionmentioning
confidence: 91%
“…This choice would be unjustified when joint effects are strongly-or more frequently-synergistic or antagonistic in comparison to SSA or when the alternate null model is better justified for a particular mixture. For organisms exposed to metal mixtures in water, joint effects of mostly binary and tertiary mixtures are in the range of 0.5 to 2 TU and approximately equally distributed between SSA and responses that are synergistic or antagonistic in comparison to this (e.g., Enserink et al, 1991;Kraak et al, 1992Kraak et al, , 1993Kraak et al, , 1994. This pattern may reflect true toxicological interactions inside the bodies of the organisms, since the metal fraction sorbed to particles is low in aquatic media (Enserink et al, 1991).…”
Section: Implications For Risk Assessmentmentioning
confidence: 96%
“…La capacité de régulation du zinc a été signalée pour des espèces de moules marines (Chan 1988, Martincic et al 1992. La moule zébrée est capable de réguler efficacement ses niveaux intracellulaires de cuivre jusqu'à une concentration dans l'eau de 13 ^g.Lau delà de ce seuil, le cuivre est accumulé (Kraak et al 1992). En revanche, le cadmium est accumulé dès qu'il est présent à de faibles teneurs dans l'eau et le relargage est très lent (Bias & Karbe 1985, Kraak et al 1992.…”
Section: Discussionunclassified
“…La moule zébrée est capable de réguler efficacement ses niveaux intracellulaires de cuivre jusqu'à une concentration dans l'eau de 13 ^g.Lau delà de ce seuil, le cuivre est accumulé (Kraak et al 1992). En revanche, le cadmium est accumulé dès qu'il est présent à de faibles teneurs dans l'eau et le relargage est très lent (Bias & Karbe 1985, Kraak et al 1992. La régulation ou, au contraire, un processus cumulatif impliquent la prise en compte de l'impact biologique de chaque élément, puisque la concentration dans le mollusque ne reflète plus nécessaire-ment celle dans l'eau.…”
Section: Discussionunclassified